2006
DOI: 10.1007/s10811-006-9040-z
|View full text |Cite
|
Sign up to set email alerts
|

Element Concentrations in Some Species of Seaweeds from La Paz Bay and La Paz Lagoon, South-Western Baja California, Mexico

Abstract: La Paz Bay and La Paz Lagoon are water bodies of the Gulf of California that are influenced by waste water discharges from the City of La Paz and from activities of the phosphorite mining company "Rofomex". Because seaweeds concentrate elements from the water and are used as effective indicators of contamination by metals, we investigated their usefulness in this region. Concentrations of certain major elements (Ca, Fe, K and Na) and trace elements (As, Ba, Co, Cr, Cs, Hf, Rb, Sb, Sc, Se, Sr, Ta, Th, U, Zn and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
10
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 23 publications
2
10
1
Order By: Relevance
“…We found significant spatial and temporal variations in heavy metal concentrations in marine plants as previous spatial studies has shown in the region (Páez-Osuna et al 2000;Sánchez-Rodríguez et al 2001;Rodriguez-Castañeda et al 2006, Rodríguez-Meza et al 2008 (Zaytsev et al 2003). These levels of Cd in seaweeds has not been observed in the Gulf of California studied populations but strong species and spatial variations where observed (Páez-Osuna et al 2000;Sánchez-Rodríguez et al 2001;Rodriguez-Castañeda et al 2006).…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…We found significant spatial and temporal variations in heavy metal concentrations in marine plants as previous spatial studies has shown in the region (Páez-Osuna et al 2000;Sánchez-Rodríguez et al 2001;Rodriguez-Castañeda et al 2006, Rodríguez-Meza et al 2008 (Zaytsev et al 2003). These levels of Cd in seaweeds has not been observed in the Gulf of California studied populations but strong species and spatial variations where observed (Páez-Osuna et al 2000;Sánchez-Rodríguez et al 2001;Rodriguez-Castañeda et al 2006).…”
Section: Discussionsupporting
confidence: 83%
“…These levels of Cd in seaweeds has not been observed in the Gulf of California studied populations but strong species and spatial variations where observed (Páez-Osuna et al 2000;Sánchez-Rodríguez et al 2001;Rodriguez-Castañeda et al 2006). The differences in heavy metal concentrations that we found in the seaweeds did not generally correspond with patterns of those elements previously observed in the sediment from the same region or seaweed species (Rodríguez-Meza et al 2008), contrary to the studied sites in the Gulf of California near a mine (Rodriguez-Castañeda et al 2006) or near industrial ports (Páez-Osuna et al 2000;Sánchez-Rodríguez et al 2001;Rodriguez-Castañeda et al 2006). This finding, together with the observed species differences, suggests that the metabolic condition and lifecycle stage of the individual species might influence metal uptake and accumulation (Lobban and Wynne 1981).…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…Previous As values reported for other ulvales fluctuated on the same levels (1.1-16 mg kg À1 dw) and were reported to be non-toxic for human health (Pérez et al, 2010;Rodrí-guez-Castañeda et al, 2006). Lead concentration ranged between 1 and 3.5 mg kg À1 dw; these values were lower than those reported in other ulvales studies (Mohamed & Khaled, 2005;Orduña-Rojas & Longoria-Espinoza, 2006 (Paez-Osuna et al, 2000;Rodríguez-Castañeda et al, 2006). Ni concentrations among samples varied from 2.37 to 5.72 mg kg À1 dw, being higher in the LSS samples but consistent with values reported by and Paez-Osuna et al (2000).…”
supporting
confidence: 76%
“…A higher Ca content was observed in Ulva produced in shrimp ponds (LSS samples) than MSS samples (average 10 vs 19 g kg À1 dw). Nevertheless, Ca content in cultivated U. clathrata was lower than those reported for E. intestinalis (25 to 122 g Ca kg À1 ) collected in the La Paz bay and lagoon in Baja California México (Rodríguez-Castañeda, Sánchez-Rodríguez, Shumilin, & Sapozzhnikov, 2006) and also lower than values reported by for other ulvales (26 to 47 g Ca kg…”
Section: Minerals Concentrationscontrasting
confidence: 56%